Roadmap for Clinical Research Work - Grande Ratti, María Florencia; Vallone, Marcelo G. (Revista del Hospital Italiano de Buenos Aires, 2023)
Following a recent publication, we take the opportunity to review the challenge of road-mapping a research project. We comment on lessons learned from our experience, emphasizing the factors that may have positively contributed to the success of this process in record time.